Kecenderungan Memakai Cadar di Kota Banda Aceh dan Aceh Besar: Kajian Living Hadis - Maizuddin, Maizuddin; Suarni, Suarni (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2019)
The article aims at describing the tendency of wearing a veil in Banda Aceh City and Aceh Besar District, which has recently increased significantly. It employs living hadith as a concept with a qualitative method that seeks to explore hadiths that living in Muslim societies, how they are applied and made into traditions in daily life. The article argues that the use of the veil was more based on self-protection than on theological motivation. However, they still held that wearing veil is a sunna. This circumcision is then understood in a totalistic ideal typology, which leads to the implementation of Sunna in a higher level of application. Besides, women who wear a veil feel more filled with religious nuance, which manifests in the attitude of ‘iffah (self-care), islah (improvement of knowledge and behavior) and ‘izzah (feeling noble). Also, the religiosity of a veiled female affects in two aspects: socio-morality and psychological aspect.